A Review of the Impact Performance of Natural Fiber Thermoplastic Composites - Thomason, James L.; Rudeiros-Fernández, José Luis (Frontiers in Materials, 2018)
Many academic studies continue to conclude that natural fibre reinforced thermoplastic composites (NFTCs) have some potential to compete with mineral/inorganic fibre and filler reinforced composites in certain applications due to their distinctive characteristics. NFTCs are often presented as a more environmentally friendly product which may, in some cases, offer useful levels of specific strength and stiffness with an overall reduced carbon footprint. However, from an end-use composite performance viewpoint, issues with impact resistance (notched and un-notched) continue to hold back the large-scale implementation of these composites. This paper presents a review of the recent work on impact properties of NFTCs, analysing the effects of fundamental composite parameters and potential routes to improvement.